Comparative efficacy and acceptability of licensed dose intranasal corticosteroids for moderate-to-severe allergic rhinitis: a systematic review and network meta-analysis - Soe, Kay Khine; Krikeerati, Thanachit; Pheerapanyawaranun, Chatkamol; Niyomnaitham, Suvimol; Phinyo, Phichayut; Thongngarm, Torpong (Frontiers in Pharmacology, 2023)
No evidence shows that one intranasal corticosteroid (INCS) is better than another for treating moderate-to-severe allergic rhinitis (AR). This network meta-analysis assessed the comparative efficacy and acceptability of licensed dose aqueous INCSs. PubMed/MEDLINE, Scopus, EMBASE, and the Cochrane Central Register of Controlled Trials were searched until 31 March 2022. Eligible studies included randomized controlled trials comparing INCSs with placebo or other types of INCSs in patients with moderate-to-severe allergic rhinitis. Two reviewers independently screened and extracted data following the Preferred Reporting Items in Systematic Reviews and Meta-analysis guideline. A random-effects model was used for data pooling. Continuous outcomes were expressed as standardized mean difference (SMD). The primary outcomes were the efficacy in improving total nasal symptom score (TNSS) and treatment acceptability (the study dropout). We included 26 studies, 13 with 5,134 seasonal AR patients and 13 with 4,393 perennial AR patients. Most placebo-controlled studies had a moderate quality of evidence. In seasonal AR, mometasone furoate (MF) was ranked the highest efficacy, followed by fluticasone furoate (FF), ciclesonide (CIC), fluticasone propionate and triamcinolone acetonide (TAA) (SMD −0.47, 95% CI: −0.63 to −0.31; −0.46, 95% CI: −0.59 to −0.33; −0.44, 95% CI: −0.75 to −0.13; −0.42, 95% CI: −0.67 to −0.17 and −0.41, 95% CI: −0.81 to −0.00), In perennial AR, budesonide was ranked the highest efficacy, followed by FF, TAA, CIC, and MF (SMD −0.43, 95% CI: −0.75 to −0.11; −0.36, 95% CI: −0.53 to −0.19; −0.32, 95% CI: −0.54 to −0.10; −0.29, 95% CI: −0.48 to −0.11; and −0.28, 95% CI: −0.55 to −0.01). The acceptability of all included INCSs was not inferior to the placebo. According to our indirect comparison, some INCSs have superior efficacy to others with moderate quality of evidence in most placebo-controlled studies for treating moderate-to-severe AR.